Witnessing Together to Christ's Compassionate Love: Report of the Moderator to the 11th Assembly of the World Council of Churches, Karlsruhe, 2022 - Abuom, Agnes (The ecumenical review, 2023)
This is the text of the address on 31 August 2022 of the moderator of the central committee of the World Council of Churches (WCC) to the WCC's 11th Assembly, which took place in Karlsruhe, Germany, from 31 August to 8 September 2022.